Gorky’s Editorial Project The History of the Civil War: On the Materials of the A.M. Gorky (IWL RAS) and RGASPI Archives - Olga V. Bystrova (Studia Litterarum, 2017)
The article focuses on the history of Maksim Gorky’s design — the publication of the History of the Civil War volumes. The analysis of Gorky’s correspondence (1929–1930) from the A.M. Gorky archives (IWL RAS) reveals that the idea of the collection emerged at the beginning of 1928. In the course of the preparatory work, the Central Committee of the CPSU(b) obliged Communist party officials, Soviet and military functionaries in all Soviet republics and regions to collect documents and memories of the Civil War, to write and review materials for the collection. Gorky conceived the volumes of The History of the Civil War to be popular and accessible to the average reader. For this purpose, he considered inviting talented Soviet authors who took part in the Civil War. Gorky’s recommendations were taken into account while forming the Editorial Board. The CC of the CPSU(b) on July 31, 1931 established the Editorial Board (comprised of Chief, Historical and Artistic Boards) that Gorky also joined. Under his guidance, the Secretariat of the Chief Editorial Board issued instructions that were intended to direct a wide range of research subjects and provide researchers with methodology. Gorky’s letters from the RGASPI collection give us idea of the huge amount of work done by the writer in the process of preparing the first volume for publication. If the first, 1935 volume reflects Gorky’s vision and concept of the collection, the subsequent 4 volumes published after his death departed from the original design. Despite this and the fact that only 5 volumes out of 15 were issued, we can state that Gorky’s design was realized and that the History of the Civil War still remains an authoritative book in the field.